KULTUR MASYARAKAT DAN HAK KEKAYAAN INTELEKTUAL - TOTOK DWINUR HARYANTO (Universitas Slamet Riyadi, 2009)
Abstract: The right comes from human intellectuals covers three things, they are: works, invention, and brand. The exclusivity of intellectua lproperty rights ban people to multiply, publish, without permition. This comes from the individual and capitalistic thought from western culture. It is different with Indonesian culture which put public and common interest as a first priority. The effort to balance the exclusive and individual right and public rights must be conducted. Keywords: intellectual rights